2020
DOI: 10.20899/jpna.6.2.182-208
|View full text |Cite
|
Sign up to set email alerts
|

Checking in on the State of Nonprofit Scholarship: A Review of Recent Research

Abstract: The complexity and diversity of the nonprofit sector provides a rich landscape for academic scholarship; and, growing numbers of nonprofit scholars and their associated research publications have established the field of nonprofit research. Yet, it is unclear if this research has been applied appropriately to the evolving landscape of the sector. Although literature reviews have helped us to understand the status of academic scholarship in the field of nonprofit research, these reviews have primarily focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
(43 reference statements)
3
12
0
Order By: Relevance
“…The categories of education and democracy are different from the previous content analysis findings conducted in the nonprofit studies field, such as Minkowitz et al (2020) and Ma and Konrath (2018). As demonstrated by answering research question three, democracy emerged in JNEL in 2015 and demonstrates the evolution of the field of nonprofit and philanthropic studies.…”
Section: Content Analysis Differencesmentioning
confidence: 72%
See 2 more Smart Citations
“…The categories of education and democracy are different from the previous content analysis findings conducted in the nonprofit studies field, such as Minkowitz et al (2020) and Ma and Konrath (2018). As demonstrated by answering research question three, democracy emerged in JNEL in 2015 and demonstrates the evolution of the field of nonprofit and philanthropic studies.…”
Section: Content Analysis Differencesmentioning
confidence: 72%
“…This paper reports on the preliminary keyword results and sorts them into main categories. Previous content analysis studies of nonprofit and philanthropic studies journals conducted by scholars (Coule et al, 2020, Ma & Konrath, 2018Marberg et al, 2019;Minkowitz et al, 2020) revealed similar themes and theories across nonprofit and philanthropic studies journals. In addition, a previous content analysis study has been conducted on one journal (Bingham & Bowen, 1994).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, Brass et al (2018) established the NGO Knowledge Collective 2 to synthesize the academic scholarship on NGOs. Studying our field's intellectual growth has been attracting more scholarly attention (Walk & Andersson, 2020;Minkowitz et al, 2020;Kang, Baek, and Kim 2021).…”
Section: Applying the Methods: The Knowledge Infrastructure Of Nonprofit And Philanthropic Studiesmentioning
confidence: 99%
“…For example, Brass et al (2018) established the NGO Knowledge Collective 2 to synthesize the academic scholarship on NGOs. Studying our field's intellectual growth has been attracting more scholarly attention (Walk and Andersson 2020;Minkowitz et al 2020;Kang, Baek, and Kim 2021).…”
Section: Natural Language Processingmentioning
confidence: 99%